Guided Bone Regeneration: CGF and PRF Combined With Various Types of Scaffolds—A Systematic Review - Francesco Inchingolo; Angelo Michele Inchingolo; Giulia Latini; Elisabetta de Ruvo; Merigrazia Campanelli; Andrea Palermo; Massimo Del Fabbro; Marco Di Blasio; Alessio Danilo Inchingolo; Gianna Dipalma (International Journal of Dentistry)
Conclusion: Despite valuable insights, further research is needed to comprehensively understand the characteristics of growth factors in various surgical interventions, ensuring informed decision-making in bone regeneration surgery.